2020
DOI: 10.1097/prs.0000000000007238
|View full text |Cite
|
Sign up to set email alerts
|

The Baker Classification for Capsular Contracture in Breast Implant Surgery Is Unreliable as a Diagnostic Tool

Abstract: Background: Breast implants are frequently used in cosmetic and reconstructive breast surgery. Capsular contracture, the most common long-term complication, is usually graded using the Baker classification. Despite its widespread use, the reliability of the Baker classification has never been established. The aim of this study was to determine the interobserver reliability and agreement of the Baker classification. Methods: Sixty women who had undergone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…In fact, studies report a prevalence of CF of 2.8 to 20.4% [2][3][4][5][6][7][8]. The degree of severity is clinically classified by the Baker score system which includes four stages [9,10]. The first stage is the least severe and is characterized by a lack of clinical symptoms, while the fourth stage represents the most severe form of CF characterized by breast deformity, stiffness, and pain.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, studies report a prevalence of CF of 2.8 to 20.4% [2][3][4][5][6][7][8]. The degree of severity is clinically classified by the Baker score system which includes four stages [9,10]. The first stage is the least severe and is characterized by a lack of clinical symptoms, while the fourth stage represents the most severe form of CF characterized by breast deformity, stiffness, and pain.…”
Section: Introductionmentioning
confidence: 99%
“…To help objectify and grade the severity, both the Baker and then Baker-Spear classifications were created. 48,49 Baker Classification Augmentation…”
Section: Clinical Implications Of Capsular Contracture Classificationmentioning
confidence: 99%
“…The grading systems mentioned above have sparked some controversy, especially in the reconstructive literature due to the fact that no validation studies have been performed. 48 One study which utilized two independent plastic surgeons found that the interobserver reliability of the Baker grading scale is quite poor. 48 This is likely due to the broad spectrum of clinical presentations associated with each strata of the classification.…”
Section: Baker-spear Classification Reconstructionmentioning
confidence: 99%
“…A limitation is that no interobserver agreement was tested for the objective examinations. A recently published study reported low interobserver agreement for grading capsular contracture according to the Baker scale, emphasising the importance of this matter [17]. In order to strengthen the role of applanation tonometry as an objective breast softness measurement tool, an assessment of the interobserver agreement is warranted.…”
Section: Fractional Area B Mean ± Sdmentioning
confidence: 99%
“…It is a four-grade scale and grades III-IV correspond to a symptomatic hard breast defined as showing capsular contracture [16]. The Baker scale is based on a combination of clinical palpation and breast appearance and is thus dependent on the examiner's experience and subjective assessment [17].…”
Section: Introductionmentioning
confidence: 99%